Pengaruh Transformational Leadership Dan Psychological Capital Terhadap Work Engagement Pada Karyawan Generasi Z - Restiani, Restiani; Puspitawati, Ira (Universitas Andalas, 2024)
Generation Z is known for frequently moving from one company to another. This is related to how Generation Z employees commit to their jobs both emotionally and intellectually within an organization or company. In other words, the issue among Generation Z employees is related to work engagement. The aim of rhis research is to determine the influence of transformational leadership and psychological capital on work engagement among generation Z employees. The population of this research is generation Z employees aged 18-27 years. In sampling, non-probability sampling techniques with purposive sampling were used. This research involved 102 generation Z employees as participants. The measuring instruments used are the Multifactor Leadership Questionnaire (MLQ) by Bass and Avolio (2004) with a realibility value of 0.953, the Psychological Capital Questionnaire – Short Version (PCQ) by Luthans, Avolio, Avey, and Norman (2007) with a reliability value of 0.817, and the Utrecht Work Engagement Scale (UWES) by Schaufeli and Bakker (2004) with a reliability value of 0.948. data collection in this research was carried out by providing an online questionnaire using google forms. The data analysis technique in this reasearch uses multiple linear regression. Based on the result of the research conducted, it shows that there is a significant influence of transformational leadership and psychological capital together on work engaggement in generation Z employees, amounting to 88,4% with a significance value of 0.000. Separately, transformational leadership has an influence of 47,9% with a significance value of 0.000 on work engagement, while psychological capital has an influence of 47,6% with a significance value of 0.000 on work engagement. Therefore,it is important to pay attention to leadership style and psychological capital to increase employee work engagement.